COMMUNITY INTERNET ACCESS IN RURAL AREAS: A STUDY ON COMMUNITY INFORMATION CENTRES IN BANGLADESH - Islam, Md. Anwarul; Gausul Hoq, Kazi Mostak (Malaysian Journal of Library and Information Science, 2010)
Information is an indispensable resource for the socio-economic development of any community as it is needed and utilized by society for its development and prosperity. The rural communities have different needs for information depending upon their functions, responsibilities and duties. Different community information centres are meeting up these demands through the provision of information services. The purpose of this article is to highlight community information centres established in the rural areas of Bangladesh and describe how these centres are playing a vital role for providing specific Internet- based information services to the rural communities. This article explores the major role of Community Information Centres (CICs) and its impact on the user communities in Bangladesh. Equal importance is also given to how the communities are getting the latest information facilities through CIC and explores how CIC can be strapped up to promote development of the rural communities in Bangladesh. This article also sees the sights of different community Internet access points in Bangladesh and identifies their service pattern and existing situations of internet services. It also highlights the different problems of CICs and an attempt has been made to suggest some effective measures and future directions for further development of Internet access points and CICs in Bangladesh.